Identification of Innovative Factors Influencing Socio-economic Local and Regional Development - Waldemar A. KUNZ (Communications of International Proceedings, 2021)
It should be noted that recently a model of regional development based on innovation processes has been increasingly crystallized. In this view, what ultimately contributes to socio-economic development is the ability of individual regions to continuously generate and adapt new technologies, organizational solutions and new knowledge. In relation to the municipality, one can also talk about new added value for the region. However, the condition is that the described processes are new and have been practically used economically with a positive economic result. Innovation should be treated as a continuous process. Taking into account the speed of assimilation of new technological ideas, progress is made continuously. A one-time improvement, even at the municipal level, will not be successful forever. This article shows the impact of innovation accelerating socio-economic development at the local and regional level. This is an important field of action, because especially in the ten worlds, you can not plan long-term development without innovative support. The innovativeness of municipalities and regions is a resultant of many processes and phenomena of socio-economic and spatial nature. It is derived, among other things, from the innovativeness of economic entities, the scientific and research sector, human and social capital or innovation policy.
Keywords: Innovation; Economy; Development; Municipalities.